Factors Associated with Abortion at the Sitti Fatimah Makassar Mother and Child Hospital - Adnin, Nur (Advances in Healthcare Research, 2023)
Purpose: This study aims to determine the factors associated with abortion at Sitti Fatimah Makassar Mother and Child Hospital. Research Design and Methodology: The research employed an analytical observational approach with a cross-sectional study design. This design was used to examine the correlation or association between independent variables and the dependent variable. The study population consisted of 107 respondents, and the sampling technique used was Random Sampling, where samples were selected randomly from the population. Findings and Discussion: The analysis of 107 respondents revealed several key findings: a significant relationship was found between age and the incidence of abortion (p = 0.005); no significant relationship was found between parity and abortion (p = 0.058); a significant relationship was identified between pregnancy spacing and abortion (p = 0.000); a significant relationship was also found between nutritional status (hemoglobin levels) and abortion (p = 0.000); and a significant relationship was established between a history of previous abortions and the current incidence of abortion (p = 0.000). Implications: These findings highlight the importance of considering factors such as age, pregnancy spacing, nutritional status, and previous abortion history in the prevention and management of abortion cases at the hospital. This could inform healthcare practices and policies aimed at reducing the incidence of abortion by addressing these associated factors.